Propriedades termodinâmicas do oscilador de Dirac e algumas contribuições da função theta de Jacobi - Pacheco, Mário Henrique Gomes (2007)
In this work we analyze the three-dimensional Dirac oscillator in a thermal bath. We found that the heat capacity is two times greather than the heat capacity of the one-dimensional Dirac oscillator in the higher temperatures. We begin with the energy spectrum of the three-dimensional Dirac oscillator, then we find the partition functions and others thermodynamics properties; thus we make one comparasion with the one-dimensional Dirac oscillator and non-relativistic harmonic oscillator. We are interested in study numerically the properties thermodynamics of the square well with infinity potencial. In the latter case we have used a Jacobi theta function.